A UNIQUE INTERPRETATION OF SOCIAL JUSTICE IN EASTERN PHILOSOPHY - Teshaboev Mukhiddin Marifovich (Journal Park Publishing, 2023)
In this article, the idea of justice, spirituality, morality, and culture in each nation and nation's civilization is manifested in different ways in relation to its history, and in some sense it is determined by the figures that determine the historical event. In Eastern philosophy, social justice itself its specific interpretation is explained.
Keywords: compliance, differentiation, social justice and equality, Zoroastrianism, Monism, Mazdakianism, Greek philosophy, God, Islamic world, government.